Dampak Efektivitas Pendidikan Tata Krama Dalam Keluarga Terhadap Pertumbuhan Karakter Anak di SDK Naileku - Mones, Anselmus Yata; Tmaneak, Laurensia (JURNAL PROPHETA, 2021)
The purpose of this research is as a basis for educating children in the familyabout etiquette, to be able to know the role of parents in teaching manners to children, toshape the child's personality into a person of character, and also as inspiration for researchers about the importance of etiquette for students to achieve better personalcharacter.This research uses a qualitative approach, with the type of case study research.The research method of data collection is more focused on using interview techniques.The research location is in Sekolah Dasar Katolik (SDK) Naileku. The data analysistechnique uses data reduction, data presentation, and data verification. The subjects ofthis research were 6 people from the school (principals and teachers), 14 students'parents, and 14 students.The findings in this study are almost all parents teach etiquette at home. They saythat manners are very important to be taught to children, and need to be instilled so thatthe child's personality can become a useful person in the family and society. Educationof manners in the family is very important for the growth of children's character atschool. Through manners, children grow into human beings with character and alsoknow to carry themselves in the school environment and in the community. There isalso another finding that there is character education in SDK Naileku. Teachers alwaysgive good directions to students. Character education is very important to be taught tostudents.Based on the results of data analysis, there is certainty that in the house parentsteach etiquette to children. Manners are always taught to children from an early age.Manners are taught with the reason that in the future the child's personality can becomea good person or a person of character. Etiquette in the family is very important andmust be taught from an early age, so that it does not have an impact on the family whenit is an adult. With the karma, the child's personality can maintain the good name of thefamily, especially the parents. Character education in the context of education inschools, is a type of education whose ultimate hope is the realization of students whohave moral integrity who can be reflected in everyday life. These values are manifestedin good interaction behavior in relationships with God, relationships with others and inrelationship with God. Character education is very important and must be instilled sincechildhood.